Pendidikan Islam dan Spirit Antikorupsi; Analisis Desain Pembelajaran PAI Berwawasan Antikorupsi di Sekolah - Nurotun Mumtahanah; Ahmad Suyuthi (Indonesian Journal of Islamic Education Studies (IJIES), 2021)
This article explains the design of anti-corruption-based Islamic religious education learning in junior high schools. Educational institutions become media for prevention as a preventive effort in tackling corrupt behavior from an early age. By using qualitative research methods, the data in this research were obtained through interviews and searching curriculum documents. This study found that the anti-corruption PAI learning design was carried out by designing primary objectives and competencies, both subjects and graduates, which referred to anti-corruption values, such as honesty, trustworthiness, trustworthy and responsible. The learning objectives are formulated through basic competencies, reinforced by contextual learning methods realized through habituation, dialogical, interactive, and integrative learning experiences. This study also found that learning evaluation was carried out through authentic assessment because anti-corruption behavior cannot be assessed only by cognitive understanding but requires observation and trust to develop a trustworthy attitude. This study provides theoretical implications that anti-corruption education in educational institutions needs to be strengthened by integrative learning designs, which increase students' understanding need an academic infrastructure that can support the birth of behavior with integrity.